Improvement Model of OEE in the Production Process of Cardboard Boxes Through SMED, TPM, Automation, and IoT - Gonzales-Vera, Rolando (2025)
As processes become more complex, measuring them using key KPI indicators, such as Overall Equipment Effectiveness (OEE), is essential. This study analyses the OEE of the cardboard box production process-the product with the highest annual revenue in a Peruvian printing company. The current OEE is 64.27%, which falls short of the graphic industry standard (72.5%). Increasing the OEE would provide several benefits, such as higher availability, improved product quality, reduced setup times, and lower machine wear. Therefore, an innovative solution model is proposed that will use SMED and TPM tools, as well as Automation and IoT technologies. These Lean tools will be enhanced through the mentioned technologies. The solution model will follow the PMBOK approach due to its significant contributions to project management and will consist of three phases: initial, implementation, and closure. Improvements will be projected for key SMART indicators that are identified. Subsequently, these improvements will be validated through simulation in Arena software across three scenarios: moderate, optimistic, and pessimistic. All three scenarios will show improvements over the current OEE, approaching the industry standard. Setup time in die-cutting was reduced to 836.69 minutes, die-cutter wear decreased to 24.58%, and lubricant usage in guillotines and offset machines increased to 255.04 ml and 569.21 ml, respectively.